TO THE DIRECTION OF BASIC EDUCATION SOURCES - SULASTRI HARUN; ABDUL RAHMAT; RUSMIN HUSAIN (International Journal of Innovations in Engineering Research and Technology, 2021)
This study aims to determine the direction of basic education philosophy sources. Where in this study describes the nature of philosophy in general, how philosophy then flows towards or the realm of education. Furthermore, how the concept of educational philosophy refers to the philosophy of basic education. This research was conducted by applying the literature study method. Literature study is done by collecting, studying and studying documents, books, notes or other literature related to the topic of research or related to educational philosophy material, especially basic education. The data collection process carried out by researchers was done by collecting various literatures such as books, articles, journals, previous studies related to the topic of Direction of Thinking of Basic Education Philosophy Sources. After that, the researcher reads the material that has been collected, then analyzes and performs analysis or coding in order to retrieve information that can be used in compiling this research. The next step is to analyze the data that has been collected, the data analysis carried out in this study is to use critical analysis which is an interpretation of the text and responds to the meaning behind an event. From the data analysis that has been carried out, the researchers found that the basic educational philosophical sources of thought are derived from the concept of philosophy in general in the form of critical thinking and human explanation in basic concepts regarding the overall phenomena of life and human thought. Then it flows towards parts of educational philosophy which then develop or focus on one of the realms, namely towards the philosophy of basic education. Where in essence, the idea of the source of basic educational philosophy originates from the main philosophy in general itself.